2016
DOI: 10.1111/bdi.12418
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐relation between brain‐derived neurotrophic factor and antioxidant enzymes in bipolar disorder

Abstract: There was a robust and independent correlation between peripheral BDNF and antioxidant enzyme activities in individuals with BD, which was moderated by metabolic comorbidities. These results reinforce the concept that these systems are associated and further extend knowledge of the putative effect of metabolic comorbidities in the pathophysiological substrates of BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 76 publications
(98 reference statements)
1
14
0
Order By: Relevance
“…For example, recent work has suggested that BMI influences the association between risk for BD and a variant in the gene encoding transcription factor 7‐like 2 (TCF7L2), which is involved in the canonical Wnt pathway . In addition, BMI and impaired glucose metabolism have been shown to impact the regulation of brain‐derived neurotrophic factor (BDNF) and antioxidant enzymes, which have in turn been independently associated with neurostructural changes . Conversely, we recently documented, using data from the REI‐PBD study, that the association between BMI and cognitive performance was risk status‐dependent, with symptomatic BD offspring displaying more pronounced impairment with increasing BMI .…”
Section: Discussionmentioning
confidence: 89%
“…For example, recent work has suggested that BMI influences the association between risk for BD and a variant in the gene encoding transcription factor 7‐like 2 (TCF7L2), which is involved in the canonical Wnt pathway . In addition, BMI and impaired glucose metabolism have been shown to impact the regulation of brain‐derived neurotrophic factor (BDNF) and antioxidant enzymes, which have in turn been independently associated with neurostructural changes . Conversely, we recently documented, using data from the REI‐PBD study, that the association between BMI and cognitive performance was risk status‐dependent, with symptomatic BD offspring displaying more pronounced impairment with increasing BMI .…”
Section: Discussionmentioning
confidence: 89%
“…The findings seem to be influenced by ethnicity, gender, stage of illness, medication, comorbidities, obesity, and smoking. [21][22][23][24][25] Interestingly, this heterogeneity also appears in studies assessing the activity of these enzymes in individuals experiencing their first episode of psychosis. 22,23 Possible differences between chronic patients with schizophrenia and individuals transitioning to psychosis have not been directly evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Immune activation and chronic mild inflammation in depression are indicated by increased plasma levels of positive acute phase proteins, e.g., haptoglobin and C-reactive protein (CRP), and increased levels of T helper cells (Th1) and M1 macrophagic cytokines [1,3,4]. Lowered levels of endogenous antioxidants and antioxidant enzymes, including high-density lipoprotein (HDL) cholesterol, vitamin E, paraoxonase (PON)1, coenzyme Q10, and zinc, are often observed in clinical depression and animal models of depression [2,[5][6][7][8][9][10]. Immune activation and chronic inflammatory processes are accompanied by increased production of reactive oxygen species (ROS) and reactive nitrogen species (RNS), such as superoxide, peroxides, nitric oxide (NO), and peroxynitrites [10][11][12].…”
Section: Introductionmentioning
confidence: 99%